Posted by **Ashley** on Friday, June 4, 2010 at 9:46pm.

-12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x

could some one check this for me please

## Answer This Question

## Related Questions

- algebra - 24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3...
- algebra - Did I do this problem the correct way if so is there a shorter way to ...
- alg2 check? - solve 3(8x-2)=46-2(12x+1) 24x-6=46-24x+2 24x-6=48-24x 48x-6=48 48x...
- Algebra - checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4...
- Math - (2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+...
- algebra - -12x^6+24x^5-18x^2/-6x^2 3x^4+x^3-3x check see if I did it right.
- Algebra (Re.: Reiny) - The fact that there was that nice symmetry to the ...
- algebra - Reduce answers to lowest terms. 1.) 2x/2x^2+5x-3 + 5/x^2-9 = 2.) x-3/...
- Math - Find the HCF of f(x) = 6x^3 + 24x^2 + 18x, g(x) = 4x^4 + 4x^3 - 24x^2
- Math - consider the equations:f(x)=-6x-1 and g(x)=4x^2 Select the solution for (...

More Related Questions